1991
DOI: 10.1143/jjap.30.l661
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Thermal Oxidation of Silicon by UV-Irradiation

Abstract: Silicon can be thermally oxidized at low temperatures under dry O2 or N2O flow with UV-irradiation. The oxide thickness is about 9.0 nm in 4 h at 500°C on dry O2+UV oxidation. The oxide formed by dry O2+UV is thicker than that formed by N2O+UV at a relatively long oxidation time. The main oxidation species are ozone for dry O2+UV and excited-state 1D oxygen atoms for N2O+UV. The quality of oxide film formed by dry O2+UV is equal to that formed by common oxidation in dry O2 without UV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…With the goal of realizing low-temperature silicon oxidation, the photooxidation method using O 2 and UV lamps has been studied intensively. [1][2][3][4][5] Fang et al 5) revealed that the oxidation rate can be as high as 8 nm/min when UV light ( ¼ 126 nm) is exposed to O 2 atmosphere. However, some film quality factors (such as the leakage current) are not as good as those of the thermal oxide.…”
mentioning
confidence: 99%
“…With the goal of realizing low-temperature silicon oxidation, the photooxidation method using O 2 and UV lamps has been studied intensively. [1][2][3][4][5] Fang et al 5) revealed that the oxidation rate can be as high as 8 nm/min when UV light ( ¼ 126 nm) is exposed to O 2 atmosphere. However, some film quality factors (such as the leakage current) are not as good as those of the thermal oxide.…”
mentioning
confidence: 99%
“…The technique has reportedly been used to deposit silicon as well as silicon-germanium alloys and enhance the thermal oxidation of silicon at greatly reduced temperatures. [21][22][23] Furthermore, in a more relevant application, low-fluence UV laser irradiation (140 mJ/cm 2 as compared to the high 450 mJ/cm 2 fluence required to melt silicon) at a wavelength of 248 nm has been observed to preferentially remove arsenic dopants away from an arsenic doped silicon substrate. 24 Based upon these findings, it is possible that UV light could also aid in the desorption of the terminating arsenic surface atoms on silicon (100) substrates.…”
Section: Resultsmentioning
confidence: 99%
“…2 For low pressure plasmas or when species are generated close to the target surface, however, reactions of metastable O atoms may be significant. There have been very few studies addressing the surface reactivity of O( 1 D), 5 but it has been speculated that reaction rates for this species may exceed those of ground-state O atoms by one to two orders of magnitude. 1 In modeling of oxygen containing plasmas, presumably because of the lack of data, O( 1 D) is either not included or the only ''reaction'' channel considered for the O( 1 D) -SiO 2 surface interaction is physical quenching to O( 3 P) with unit probability.…”
Section: Introductionmentioning
confidence: 99%